The Evaluation of the Effective Diameter (Deff) Calculation and its Impact on the Size-Specific Dose Estimate (SSDE) - C. Anam; F. Haryanto; R. Widita; I. Arif; G. Dougherty (Atom Indonesia, 2017)
Information on the effective diameter (Deff) is essential for estimating the dose for patients undergoing CT examinations. The purpose of this study was to calculate the effective diameter using the maximum values of lateral (LAT) and anterior-posterior (AP) diameters (Deff,m) and using LAT and AP diameters taken from the center of the image (Deff,c), and compared both estimates to the effective diameter calculated directly from the cross-sectional area of the patient (Deff,A). We evaluated 164 patients who underwent the four most frequent CT examinations, namely pelvic, abdominal, thoracic, and head examinations, using a multi-detector CT (MDCT), the Toshiba Aquilion 128. We calculated the percentage differences between Deff,c and Deff,m from Deff,A. We also used the Wilcoxon-Mann-Witney U test to statistically determine whether differences were significant. While Deff,m is statistically no different (p > 0.05) from Deff,A, Deff,c is statistically different (p ˂ 0.05) from Deff,A except for head examinations.Received: 31 May 2016; Revised: 14 December 2016; Accepted: 20 January 2017